Non‐destructive evaluation of AlSi10Mg prismatic samples generated by selective laser melting: Influence of manufacturing conditions: Zerstörungsfreie Untersuchungen an mittels selektiven Laserschmelzens hergestellten prismatischen Proben: Auswirkungen und Einflüsse der Prozessführung. Issue 5 (17th May 2016) - Hitzler, L.; Janousch, C.; Schanz, J.; Merkel, M.; Mack, F.; Öchsner, A.
Abstract : Before utilising selective laser melting in real applications, the process as well as the outcome component and its characteristics need to be fully understood. Based on the layer‐wise fabrication, with its distinctive orientations in translations and thermal influences within this additive manufacturing process, the obtained material properties and the microstructure are anticipated to be anisotropic. The selective laser melting process involves: the laser movement pattern in plane and rotation between single layers; recoater movement; substrate plate heating and movement; laser irradiation from the top; and inert gas flow. In order to gain insight into the process and its related characteristics, different sets of prismatic specimens in terms of orientation and inclination were produced and evaluated. The evaluation contained surface quality investigations with two independent measurement approaches, i.e. tactile and optical, density measurements based on the Archimedes principle and micro‐section evaluation. Furthermore, ultrasonic analyses were conducted to study the feasibility of determining the mechanical properties, i.e. Young's modulus and Poisson's ratio, in accordance with the recorded longitudinal and transversal sonic velocities. The chosen raw material for these investigations was AlSi10Mg and the fabricated parts exhibited a high relative density of at least 99.5 %. Remarkable deviations were evident in the obtained surface quality and clear trends could be determined based on the inclination and orientation condition of the sample during manufacturing. In regards to the ultrasonic investigation, it was found that the reported inherent anisotropy of selective laser melted samples could not be detected with the non‐destructive ultrasonic investigation, and destructive procedures, to date, represent the only reliable method to accurately reveal the material characteristics.